Assessment of Soil Nutrient Status under Different Cropping Systems in Khotang, Nepal - Devkota, Pawan; Aryal, Dipendra; Khanal, Baburam (International Journal of Applied Sciences and Biotechnology, 2019)
Availability of plant nutrients in rhizosphere is directly influenced by types of crop grown and land use pattern. The experiment was conducted in Diktel Rupakot Majhuwagadhi Municipality, Khotang, Nepal to assess the soil nutrients dynamics as influenced by different cropping system. Five different cropping systems (Rice – Wheat, Maize – Millet, Maize – Vegetables, Ginger and Cardamom) were selected as treatments and all treatments were replicated for five times for blocking in Randomized Complete Block Design. Soil samples from 0-15 cm depth were collected from each site and evaluated for soil pH, soil organic carbon (SOC), total nitrogen (N), available phosphorus (P), and available potassium (K). All the tested parameters except N were found to be significantly affected by cropping system. Soil in all five cropping systems were found acidic (pH<6.5) in nature with pH ranging from 5.180-6.640. The SOC was recorded highest (3.102%) from Cardamom based system and lowest amount of SOC was observed in Ginger based system. The highest amount of P (32.14 mg/kg) was reported in Maize – Vegetables cropping system and lowest P content (5.72 mg/kg) was recorded from Cardamom based system. P content in Ginger based system (31.51 mg/kg) was statistically at par with that of Rice – Wheat system. The highest K content (306.50 mg/kg) was recorded from Maize – Vegetable cropping system and lowest K content (34.80 mg/kg) was observed in Cardamom based system which is statistically similar to Rice –Wheat (35.70 mg/kg) and Maize –Millet systems (77.20 mg/kg). The result indicated that cropping systems have huge impact on plant nutrient dynamics in soil. Int. J. Appl. Sci. Biotechnol. Vol 7(3): 341-346